Synchronization and stability control of dual-motor intelligent steer-by-wire vehicle. (November 2020) - Zou, SongChun; Zhao, WanZhong
Highlights: A novel redundant dual-motor intelligent steer-by-wire system is presented. A synchronization control strategy is proposed based on cross-coupling control structure and sliding mode control algorithm. A sliding mode speed synchronization controller is designed to enhance the synchronization of the dual-motor. A mixed H2 /H∞ robust controller is designed to improve the vehicle stability and tracking performance. The hardware-in-the-loop experiment verify the effectiveness of the control strategy proposed in this paper. Abstract: In order to improve the safety of steer-by-wire (SBW) system, a dual-motor SBW system is proposed to enhance the fault tolerance and reliability of the system. However, the dual-motor SBW vehicle often loses its stability due to the external interference, and the asynchronous response between the dual-motor will further deteriorate the stability of the vehicle. Aiming at the existing problems, this paper proposes a hierarchical control strategy, in which the upper layer controls the vehicle stability and the lower layer controls the synchronization of the dual-motor. Firstly, the models of dual-motor SBW system and the vehicle are established. Secondly, considering the interference of lateral wind, sensor noise and the limitation of control output, a yaw rate controller is designed in the upper layer based on the mixed H2 /H∞ robust control theory to improve the stability and tracking performance of the vehicle. Thirdly, a sliding mode speed synchronization control strategy is proposed in the lower layer based on the cross-coupling control structure and the sliding mode control algorithm to enhance the synchronization performance between the dual-motor. Finally, the simulation is carried out by using Carsim/Simulink and the hardware-in-the-loop experiment is conducted based on the dual-motor SBW experimental station. The simulation and experimental results verify the effectiveness of the control strategy proposed in this paper.